PENGAWASAN ISI ULANG AIR TERHADAP GALON BERMEREK DI DISPERINDAG KOTA MALANG: Kajian Hukum Positif Dan Hukum Islam - Ardhian, M Aris (Jurisdictie: Jurnal Hukum dan Syariah, 2017)
The purpose of this research is to know how the supervisory Disperindag against water refill using a branded gallon in Malang, according to the study of the positive law in force and also according to Islamic law. This research is also called with the research field research. The results showed that Disperindag yet to carry out surveillance of Malang against charging process water use branded a gallon. This is contrary to the positive law and Islamic law in Indonesia, which mentions that the Disperindag must do an oversight process goes by the effort of filling water in the city of Malang.